Effectiveness of Administrative Services in SMK Negeri 1 Kakas - Sondakh, Vini Beatrix; Pangkey, Itje; Mokat, Jetty E. H. (Technium Social Sciences Journal, 2025)
This study aims to describe and analyze the effectiveness of administrative services at SMK Negeri 1 Kakas. Academic administration services at SMK Negeri 1 Kakas are carried out based on procedures and technical guidelines from the Directorate of Vocational High Schools (SMK), Directorate General of Vocational Education, Ministry of Education, Culture, Research and Technology. These services include managing student and teacher data, preparing lesson schedules, archiving important documents, and administration related to academic activities such as legalization of diplomas, administration of field work practices, and skills competency tests. The research method used is descriptive qualitative with data collection techniques through direct interviews with informants involved in academic administration services and service users. The results showed that academic administration services at SMK Negeri 1 Kakas have not been effective. Some of the influencing factors include uncoordinated procedures and division of academic administration tasks due to weak communication between administrative staff, the process of working on academic administration which is still manual so that it takes a long time, and the high workload which often causes errors or negligence in completing the administration. In addition, the facilities and infrastructure supporting academic administration services are also inadequate, characterized by limited computer equipment and printers that function properly. Currently, there is only one laptop, one computer, and one printer that can still be used optimally, while other devices are in poor condition. In terms of human resources, the number of academic administration staff is also very limited and not proportional to the workload of academic administration in a fairly dense and complex SMK environment, so ideally more than two administrative staff are needed to support the smooth running of services. This study recommends the need to improve the quality of coordination between administrative staff, modernize digital-based academic administration systems, add adequate infrastructure, and adjust the number of administrative staff according to the ideal needs of vocational schools. Thus, it is expected that academic administration services at SMK Negeri 1 Kakas can run more effectively, efficiently, and be able to accommodate the academic needs of schools quickly, precisely, and professionally.